part 2,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,

Algebra
Tutor: None Selected Time limit: 1 Day

Mar 6th, 2015

f(x) = 3x^2 - 4   when   x = 2

f(2) = 3(2)^2 - 4 = 3(4) - 4 = 12 - 4 = 8

f(x) = 5x^2 + 6x + 1    when   x = 3

f(3) = 5(3)^2 + 6(3) + 1 = 5(9) + 18 + 1 = 45 + 18 + 1 = 64

f(x) = 6x^2 + 3x - 11    when  x = -2

f(x) = 6(-2)^2 + 3(-2) - 11 = 6(4) - 6 - 11 = 24 - 17 = 7

Mar 6th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Mar 6th, 2015
...
Mar 6th, 2015
May 26th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer